Expression Authenticity: The Role of Genuine and Deliberate Displays in Emotion Perception - Zloteanu, Mircea; Krumhuber, Eva G. (Frontiers in Psychology, 2021)
People dedicate significant attention to others’ facial expressions and to deciphering their meaning. Hence, knowing whether such expressions are genuine or deliberate is important. Early research proposed that authenticity could be discerned based on reliable facial muscle activations unique to genuine emotional experiences that are impossible to produce voluntarily. With an increasing body of research, such claims may no longer hold up to empirical scrutiny. In this paper, expression authenticity is considered within the context of senders’ ability to produce convincing facial displays that resemble genuine affect and human decoders’ judgments of expression authenticity. This includes a discussion of spontaneous versus posed expressions, as well as appearance- versus elicitation-based approaches for defining emotion recognition accuracy. We further expand on the functional role of facial displays as neurophysiological states and communicative signals, thereby drawing upon the encoding-decoding and affect-induction perspectives of emotion expressions. Theoretical and methodological issues are addressed with the aim to instigate greater conceptual and operational clarity in future investigations of expression authenticity.